Analisis Kompetensi Sosial Guru Sekolah Dasar Gugus IV Kecamatan Sukajadi Kota Pekanbaru - Yasiko, Dinni; Guslinda, Guslinda; Syahrilfuddin, Syahrilfuddin (Indonesian Research Journal on Education, 2021)
This study aims to analyze the social competence of elementary school teachers in cluster IV,Sukajadi District, Pekanbaru City. The type of research used in this research is descriptiveresearch with a quantitative approach (descriptive-quantitative). The population in this studyconsisted of teachers totaling 47 people. The sample in this study was 47 people. The results of thestudy on indicators of being inclusive, acting objectively, and not discriminating because ofconsiderations of gender, religion, race, physical condition, family background andsocioeconomic status were 85.02% with the category "Very Good" , the indicator ofcommunicating effectively, empathically and politely with fellow educators, education staff,parents and the community is 75.64% with the "Good" category. the indicator of communicatingwith the professional community itself and other professions orally and in writing or in otherforms is 82.02% with the “Very Good” category, and the indicator of communicating with theprofessional community itself and other professions orally and in writing or in other forms is82.02% with the category "Very Good". Based on the description of the data analysis, it can beseen that there is a social competence of elementary school teachers in cluster IV SukajadiDistrict, Pekanbaru City with a percentage gain of 79.65% with the category "Good".